A CASE REPORT OF SUCCESSFUL TREATMENT OF STAGE IV EWING’S SARCOMA IN AN ADOLESCENT PATIENT - O. I. Kit; D. Yu. Yurchenko; D. V. Burtsev; S. A. Kuznetsov; O. P. Popovyan; A. A. Barashev; P. V. Chernogorov; E. M. Frantsiyants; A. B. Sagakyants; L. B. Kushtova; G. A. Mkrtchyan; A. I. Bespalova; et al. (Сибирский онкологический журнал)
Background. Ewing’s sarcoma is one of the most common musculoskeletal cancers in children and adolescents. Extremely aggressive clinical course of Ewing’s sarcoma makes a successful treatment of this tumor difficult. Despite a comprehensive multidisciplinary approach to the treatment of this cancer, including chemotherapy, surgery and radiation therapy, rapid tumor progression, recurrence and resistance to chemotherapy are still common.Our purpose was to present the results of a personalized approach to multidisciplinary combination treatment for musculoskeletal cancer involving polychemotherapy, 3D conformal radiation therapy and modern surgical technologies.Description of the clinical case. A female patient presented to Rostov Research Institute of Oncology complaining of a tumor and moderate pain in soft tissues of the left iliac region, left lower extremity, and lameness when walking. After complete examination, the patient was diagnosed with Ewing’s sarcoma of the left ilium with lung metastases (Т3N0M1). The patient received 6 cycles of neoadjuvant chemotherapy according to EURO EWING 2008 protocol; tumor progression and lung metastasis were registered. Two cycles of second-line chemotherapy were performed; by the decision of the doctors’ council, the first stage of surgical treatment was performed: resection of the left ilium and the defect replacement with a temporary cement spacer. In the postoperative period, the patient underwent 8 cycles of adjuvant chemotherapy, external beam radiation therapy to the lungs (12 Gy total dose) and the primary tumor (46 iGy total dose), and 12 cycles of supporting therapy. A delayed second reconstructive stage of surgical treatment involved removal of a temporary cement spacer and implantation of an individual pelvic stability system. The patient was followed-up for 25 months after the combination treatment, had no complaints, and was able to ambulate without assistance; the motor function of the left hip joint was fully preserved. Conclusion. The use of non-standard high-technology approaches to surgical treatment of unfavorably localized Ewing’s Sarcoma in combination with chemo-radiation therapy allows patients with advanced tumors to achieve satisfactory results and good quality of life.